DEVELOPMENT OF RISK BASED DECISION MAKING USING EXPERT OPINION FRAMEWORK FOR MOBILE MOORING SYSTEM - SILVIANITA, SILVIANITA (2012)
The second aim of this study is to develop a Methodology for Investigation of Risk Based Maintenance (MIRBA) by using Bow Tie Analysis in order to classify the risk level and mitigation plan, and to select the best maintenance strategy using AHP (Analytic Hierarchy Process). Bow tie analysis is the combination method of the FTA on the left side and ETA on the right side. Bow tie analysis is used to classify the risk level of the mooring system. In order to select the best maintenance strategy for mooring system that has multi criteria to be considered, AHP is applied to determine the best maintenance strategy on the basis of likelihood and consequence. This study conducts risk-based decision making coupled with the knowledge of the experts of mooring system to evaluate the frequency of failure, class of consequence, mitigation measurements and maintenance strategy based on their knowledge and experience.